Effects of Acupuncture Therapy on MCI Patients Using Functional Near-Infrared Spectroscopy - Ghafoor, Usman; Lee, Jun-Hwan; Hong, Keum-Shik; Park, Sang-Soo; Kim, Jieun; Yoo, Ho-Ryong (Frontiers in Aging Neuroscience, 2019)
Acupuncture therapy (AT) is a nonpharmacological method of treatment that has been applied to various neurological diseases. However, studies on its longitudinal effect on the neural mechanisms of patients with mild cognitive impairment (MCI) for treatment purposes are still lacking in the literature. In this clinical study, we assess the longitudinal effects of ATs on MCI patients using two methods: i) Montreal Cognitive Assessment test (MoCA-K, Korean version), and ii) the hemodynamic response (HR) analyses using functional near-infrared spectroscopy (fNIRS). fNIRS signals of a working memory (WM) task were acquired from the prefrontal cortex. Twelve elderly MCI patients and twelve healthy people were recruited as target and healthy control (HC) groups, respectively. Each group went through an fNIRS scanning procedure three times: The initial data were obtained without any ATs, and subsequently a total of 24 AT sessions were conducted for MCI patients (i.e., MCI-0: the data prior to ATs, MCI-1: after 12 sessions of ATs for 6 weeks, MCI-2: another 12 sessions of ATs for 6 weeks). The mean HR responses of all MCI-0~2 cases were lower than those of HCs. To compare the effects of AT on MCI patients, MoCA-K results, temporal HR data, and spatial activation patterns (i.e., t-maps) were examined. In addition, analyses of functional connectivity and graph theory upon WM tasks were conducted. With ATs, i) the averaged MoCA-K test scores were improved (MCI-1, p = 0.002; MCI-2, p = 2.9e-4); ii) the mean HR response of WM tasks were increased (p < 0.001); and iii) the t-maps of MCI-1 and MCI-2 were enhanced. Furthermore, an increased functional connectivity in the prefrontal cortex in both MCI-1/MCI-2 cases in comparison to MCI-0 was obtained (p < 0.01), and an increasing trend in the graph theory parameters was observed. All these findings reveal that ATs have a positive impact on improving the cognitive function of MCI patients. In conclusion, ATs can be used as a therapeutic tool for MCI patients as a nonpharmacological method. (Clinical trial registration number: KCT 0002451, https://cris.nih.go.kr/cris/en/)